Healthy-related quality of life in patients with cervical cancer in Southwest China: a cross-sectional study - Min Zhao; Lei Luo; Chun-hong zhang; Jin-ping zhang; Jia-yan Yuan; Rong-yan Gu; Song-rui Ding (BMC, 2021)
Abstract Background Cervical cancer is the second most common female malignant tumor in the world. According to a study in 2018, the incidence of cervical cancer in Yunnan Province of China was 11.42 per 100,000, the mortality rate was 3.77 per 100,000, and higher than the national average. Health-related quality of life (HRQoL) can be used not only in the selection and effect evaluation of clinical treatment plans of cervical cancer, but also in the evaluation of prognosis and long-term survival status. In this study, 288 cervical cancer patients admitted to the Yunnan Cancer Hospital in Southwest China from 2018 to 2020 were used as the survey objects to understand the HRQoL of cervical cancer patients and explore the related factors that affect HRQoL. Methods The Chinese version of the functional assessment of cancer therapy-cervix (functional assessment of cancer therapy-cervix v4.0, FACT-Cx V4) was used to investigate 288 patients with cervical cancer in Yunnan Province. Statistical analysis was performed using t-test, analysis of variance, multiple linear regression and other methods. Results The total FACT-Cx score of cervical cancer patients was (130.16 ± 14.20), the physical well-being (PWB) score was (22.02 ± 4.47), the social/family well-being (SWB) score was (25.66 ± 3.59), the emotional well-being (EWB) score was (19.75 ± 3.54), the functional well-being (FWB) score was (16.91 ± 5.01) and the additional focus area (cervical cancer subscale, CxS) score was (45.78 ± 4.61). From the multi-factor analysis results, the scores of PWB, FWB, Cxs and the total FACT-Cx were related to the choice of different treatment methods, the PWB scores of patients with concurrent chemoradiotherapy was low(β = − 1.67, P = 0.003), the FWB scores of patients with concurrent chemoradiotherapy was low(β = − 2.02, P = 0.001), the CxS scores of patients with concurrent chemoradiotherapy was low(β = − 1.61, P = 0.006), the total score of FACT-Cx of patients with concurrent chemoradiotherapy was low(β = − 5.91, P = 0.001). SWB score was affected by marital status, married patients had high PWB scores(β = 5.44, P = 0.006). The patients with heavy disease expenditures as aproportion of family disposable income(β = − 3.82, P = 0.002) and aged 60 and above(β = − 3.29, P = 0.003) had lower FWB scores. The total score FACT-Cx of patients participating in cervical cancer screening was higher(β = 7.61, P = 0.001). Conclusion The choice of treatment method is the common influencing factor of PWB, FWB, Cxs and the total FACT-Cx. Disease expenditures as a proportion of family disposable income, the treatment method, the marital status and whether to participate in cervical cancer screening affect the patient's evaluation of their own HRQoL. Medical staff should pay special attention to the choice of different treatment methods, popularize vaccination knowledge and cervical cancer screening, give more humanistic care and health education to cervical cancer patients who have low education level, poor economic conditions, divorced or separated, and encourage patients to participate in active treatment to improve the health-related quality of life.